2016
DOI: 10.1016/j.socscimed.2016.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Development, validation, and performance of a scale to measure community mobilization

Abstract: Rationale Community mobilization approaches (CMAs) are increasingly becoming key components of health programming. However, CMAs have been ill defined and poorly evaluated, largely due to the lack of measurement tools to assess mobilization processes and impact. Objective We developed the Community Mobilization Measure (CMM), composed of a set of scales to measure mobilization domains hypothesized to operate at the community-level. The six domains include: shared concerns, critical consciousness, leadership,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 44 publications
1
52
0
Order By: Relevance
“…Although the development of scales measuring community capability through numerous elements continues to evolve [4, 9, 9294], health systems research engaged with community participation remains relatively untouched by these developments. Our review found the extent of information related to community capability reported by health systems research articles with rich accounts of community participation to be very low and often of poor quality.…”
Section: Discussionmentioning
confidence: 99%
“…Although the development of scales measuring community capability through numerous elements continues to evolve [4, 9, 9294], health systems research engaged with community participation remains relatively untouched by these developments. Our review found the extent of information related to community capability reported by health systems research articles with rich accounts of community participation to be very low and often of poor quality.…”
Section: Discussionmentioning
confidence: 99%
“…While illustrative of the potential applicability of such community empowerment indices, the CCI does not address capabilities as they relate to health [17]. Lippman and colleagues recently developed an instrument to assess community mobilization in the context of HIV programming [18] that includes 7 domains. In Zambia, Underwood and colleagues measured and validated community capacity through 6 community-generated domains, to assess the roles of these domains in the context of health communication interventions focused on developing community capacity [19].…”
Section: Introductionmentioning
confidence: 99%
“…11 This gap is partially due to poor attention to theoretical conceptualization and is also the result of a lack of validated measures of CM processes. 40 Using our validated CM measure 32 we were able to empirically test changes in reported community mobilization. Mean mobilization measures did not go up significantly over time in the intervention villages as was expected; this could represent a secular trend towards more disenfranchisement and growing disillusionment in the area (note that scores often dropped more excessively in the control than in the intervention villages), or simply a lack of power to detect effects with an n = 22.…”
Section: Discussionmentioning
confidence: 99%
“…Although the other domains, such as leadership, were not associated with HIV testing in this short intervention, this was also more difficult to cultivate in a short time frame. 10,32 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation